Ionic liquid Mediated Pd-catalyzed sonochemistry for facile synthesis of carbazoles: Molecular Modelling and antimicrobial studies - Imamhusen Jamadar; Athmanand Anchi; Shruti S. Malunavar; Rajesh G. Kalkhambkar; Suraj M. Sutar; Shrinivas D. Joshi (Tetrahedron Green Chem, 2024)
Herein we have described the Pd-catalyzed sonochemistry driven by [BMIM]-IL as re-useable solvent to synthesize various carbazole scaffolds from 2,2′-dibromodiphenyl. Diverse primary amines were utilised as coupling partners in the presence of [PAIM][NTf2], which exhibits an impactful promoter in the IL medium, thereby avoiding the need for hazardous VOC's. The recyclability of ionic liquids highlights the green approach of the reaction. Further, the synthesized carbazole scaffolds were assessed for antimicrobial activity. Compounds 3e and 3g are found to be highly active. The most probable binding sites for these scaffolds were screened through a computer-simulated docking method with targeted protein.